An innovative approach for numerical simulation of stress relaxation of structural cables. (October 2017) - Wang, Xiaoxiang; Chen, Zhihua; Yu, Yujie; Liu, Hongbo
Abstract : Simplified finite element modeling method for stress relaxation simulation of structural cables was proposed. A simplified relation between steel wire stress relaxation and creep was worked out. Semi-parallel wire strands and spiral strands with different diameters were all simulated under different initial stress levels. Relaxation rate of semi-parallel wire strands and spiral strands were both larger than that of single steel wire. Semi-parallel wire strands had a decreasing trend on relaxation rate along with cable dimension. Spiral strands had slight relaxation increase along with cable dimension. Abstract: Relaxation test on cable with large diameter is usually difficult and money consuming due to its extremely large ultimate tensile strength. A simplified finite element modeling method for stress relaxation simulation of steel wire, semi-parallel wire strands and spiral strands was proposed. Simplified relationship between stress relaxation and creep of steel wires was derived and a simplified modeling method on spiral wire composition was proposed. The whole numerical approach incorporated the steel wire creep model and the simplified cable compositions to realize the simulation of stress relaxation behavior of structural cables. The effectiveness of proposed creep calibration and cable stress relaxation simulations were verified through relaxation test data of single-wires and 19-wire semi-parallel wire strands. The 19-wire, 37-wire, 61-wire, 91-wire and 127-wire semi-parallel wire strands and spiral strands at different initial stress levels were all simulated. Due to the spiral wire composition and corresponding gradient wire stress distribution under axial tension, relaxation rate of semi-parallel wire strands and spiral strands were all larger than that of single steel wire. Semi-parallel wire strands presented a decreasing relaxation rate with the increase of cable dimension. Spiral strands had larger relaxation rate than similar-sized semi-parallel wire strands, and present a slight relaxation increase trend with cable dimension. The proposed finite element modeling method can realize the stress relaxation analysis of large diameter structural cables, with only stress relaxation test data of single wires or small diameter cables. Graphical abstract: Stress relaxation of semi-parallel wire strands with different diameters were simulated under different initial stress levels, and stress distribution of wires as well as relaxation development were presented